Economic burden of managing oral cancer patients in Sri Lanka: a cross-sectional hospital -based costing study - Paul A Scuffham; Sanjeewa Kularatna; Hemantha Amarasinghe; Ruwan Duminda Jayasinghe; Dilantha Dharmagunawardene; Manjula Attygalla; Newell Johnson (BMJ Open)
Objective Cancer of the oral cavity is the leading malignancy among males in Sri Lanka, and sixth among women. This study aimed to estimate costs of managing patients with oral cancer (OCA) in Sri Lanka for a 12 month period from diagnosis.Design Hospital based costing study.Settings Four selected cancer treatment centres in Sri Lanka.Participants Sixty-nine OCA patients: 60 were males and 12 had recurrent tumours.Outcome Societal perspectives (healthcare, household and indirect costs) were itemised. Costs to the healthcare system included surgery, Intensive Care Unit (ICU) care, chemotherapy and radiotherapy. Capital costs including apportioned value of land, buildings, equipment and furniture. Household costs consisted of out of pocket expenditure for healthcare and indirect costs of lost income. Costs were estimated from the stage of presentation for treatment to 1 year of follow-up.Results Mean cost of managing a single stage II OCA patient for 1 year was Sri Lankan rupees (SLR) 58 979 (US$394, at the midyear exchange rate in 2016) to the health system. Mean household cost was SLR 77 649 (US$518). The annual cost of managing a stage III or IV patient was SLR 303 620 (US$2027), with household costs of SLR 71 932 (US$480).Conclusions Owing to the high incidence of OCA in Sri Lanka, the economic costs associated with these diseases are enormous, resulting in negative impacts on both the healthcare system and individual families, seriously impacting the country’s economy. Policy-makers should take note of this burden and increase steps for prevention and control of this devastating disease.